(untitled) (Research, Society and Development, 2020)
This article aims to analyze the conceptual representations of science and technology expressed by students of a high school technical course at the Federal Institute of Alagoas - Ifal, exploring the similarities, differences and complementarities of the concepts developed by the students. As science and technology are structural axes of Professional and Technological Education, the article aims to understand whether the subjects, inserted in this teaching modality, present critical conceptions regarding these axes as social constructs and their implications in the job market. It was possible to structure, based on the answers, two major thematic axes around the concept of science ("resolutive" (practical) and "comprehensive" (theoretical)) and two others around the concept of technology ("creation and improvement of artifacts" ”And“ social dimension ”). The analyzes demonstrate that the subjects make an interrelation between the concepts of science and technology, establishing cause and effect relations between both. We also investigated the students’ perception of the impact of science and technology on the labor market and two other thematic axes emerged (“work automation” and “advancement and dependence” [of technology]), in which students recognize the advances provided by science and technology to the world of work and show concern about structural unemployment driven by these same advances. The study is qualitative and its data, collected through questionnaires, were interpreted using the Content Analysis methodology.